Temporal-spatial characteristics and source apportionment of PM2.5 as well as its associated chemical species in the Beijing-Tianjin-Hebei region of China. (February 2018) - Gao, Jiajia; Wang, Kun; Wang, Yong; Liu, Shuhan; Zhu, Chuanyong; Hao, Jiming; Liu, Huanjia; Hua, Shenbing; Tian, Hezhong
Abstract: PM2.5 and its major chemical compositions were sampled and analyzed in January, April, July and October of 2014 at Beijing (BJ), Tianjin (TJ), Langfang (LF) and Baoding (BD) in order to probe the temporal and spatial characteristics as well as source apportionment of PM2.5 in the Beijing-Tianjin-Hebei (BTH) region. The results showed that PM2.5 pollution was severe in the BTH region. The average annual concentrations of PM2.5 at four sampling sites were in the range of 126–180 μg/m 3, with more than 95% of sampling days exceeding 35 μg/m 3, the limit ceiling of average annual concentration of PM2.5 regulated in the Chinese National Ambient Air Quality Standards (GB3095-2012). Additionally, concentrations of PM2.5 and its major chemical species were seasonally dependent and demonstrated spatially similar variation characteristics in the BTH region. Concentration of toxic heavy metals, such as As, Cd, Cr, Cu, Mn, Ni, Pb, Sb, Se, and Zn, were higher in winter and autumn. Secondary inorganic ions (SO4 2−, NO3 −, and NH4 + ) were the three-major water-soluble inorganic ions (WSIIs) of PM2.5 and their mass ratios to PM2.5 were higher in summer and autumn. The organic carbon (OC) and elemental carbon (EC) concentrations were lower in spring and summer than in autumn and winter. Five factors were selected in Positive Matrix Factorization (PMF) model analysis, and the results showed that PM2.5 pollution was dominated by vehicle emissions in Beijing, combustion emissions including coal burning and biomass combustion in Langfang and Baoding, and soil and construction dust emissions in Tianjin, respectively. The air mass that were derived from the south and southeast local areas around BTH regions reflected the features of short-distant and small-scale air transport. Shandong, Henan, and Hebei were identified the major potential sources-areas of secondary aerosol emissions to PM2.5 . Graphical abstract: Image 1 Highlights: We present the temp-spatial PM2.5 variations at four cities in BTH region of China. PM2.5 concentrations and its species show spatially similar variation in BTH region. PMF results indicate PM2.5 pollution is dominated by vehicle emissions in Beijing. Coal combustion plays a significant contribution on PM2.5 in LangFang and Baoding. Soil and construction dust constitute most important components of PM2.5 in TianJin. Abstract : PM2.5 mass and its major chemical composition in the BTH region were seasonally dependent and demonstrated spatially similar variation characteristics. PMF results indicated that PM2.5 was dominated by vehicle emissions in Beijing, coal and biomass combustion emissions in Langfang and Baoding, and soil and construction dust emissions in Tianjin, respectively.